BiOI solar cells. Issue 116 (6th November 2015) - Sfaelou, S.; Raptis, D.; Dracopoulos, V.; Lianos, P.
Abstract : An inorganic solar cell was constructed using a thin compact supporting layer of titania with BiOI nanoflakes as a functional material, a Pt/FTO cathode and a I3 − /I − redox electrolyte. Abstract : An inorganic solar cell was constructed using a thin compact supporting layer of titania with BiOI nanoflakes as a functional material, a Pt/FTO cathode and a I3 − /I − redox electrolyte. The efficiency of the cell was 1.03% but this leaves a lot of ground for improvement, which is mainly expected to come from the optimization of the BiOI nanostructure.